A Modified Vector Space Model For Protein Retrieval. - Abual-Rub, Mohammed Said; Abdullah, Rosni; Abdul Rashid, Nur'Aini (Dr. Sang H. Lee, 2007)
This paper provides an enhancement of an existing method of information retrieval which is a modification of Vector Space Model for information retrieval. This enhanced model is modified to be applied on protein sequence data whereas the normal vector space model has been applied on text data. The results show that the enhanced model achieved very good results in performance but the setup time is somehow high for a large collection of protein sequences